EDUKASI PENCEGAHAN ANEMIA PADA REMAJA PUTRI DAN PENINGKATAN PERAN GURU UKS DALAM PENDAMPINGAN MINUM TABLET TAMBAH DARAH (TTD) DI SMPN 1 KECAMATAN KAMPAR KABUPATEN KAMPAR - Yola Humaroh (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2026)
Adolescence is a nutritionally vulnerable period due to various factors. Adolescent girls are one of the groups at high risk of developing anemia. Data from Riskesdas 2018 show that the prevalence of anemia among adolescents increased from 18.40% in 2013 to 32% in 2018. The purpose of this activity was to provide education on anemia prevention and to strengthen the role of School Health Unit (UKS) teachers in assisting adolescent girls in consuming Iron Supplement Tablets (TTD) at SMPN 1 Kampar. The method used was community education through learning sessions utilizing video media, posters, booklets, and flipcharts, as well as assistance in TTD consumption using monitoring cards. The target of this activity was 60 eighth-grade female students of SMPN 1 Kampar. Initial screening through hemoglobin level examination showed that most students had normal hemoglobin levels (88.3%), although some were still found to have mild and moderate anemia (11.6%). The results showed an increase in students’ knowledge about anemia from 50.3% to 78.8% after the educational intervention. In addition, UKS teachers actively assisted the students in consuming TTD every Friday using monitoring cards. This activity successfully improved adolescent girls’ knowledge about anemia prevention, increased their adherence to consuming TTD, and strengthened the active role of UKS teachers in providing assistance.